The Divorce Phenomenon in Cenggu Village: Psychological Impact and Childcare Responsibilities - Rabiatul Adawiah (Legitima : Jurnal Hukum Keluarga Islam, 2024)
Purpose – Islam allows divorce if the household is truly untenable due to continuous conflict. However, there are many things that must be considered after the divorce, such as the ex-wife's right to maintenance and childcare. The most vulnerable party to the negative impact of divorce is the child, especially the psychological impact. This article aims to determine the psychological impact of children and parental care responsibilities after divorce in Cenggu Village. Methods – This research is descriptive-analytical qualitative research with a juridical-empirical approach. Primary data in the study are families who have divorced in Cenggu Village including husbands, wives, and children. Secondary data in this study are references from journals, books, and theses. The data collection techniques used are observation and interview. Findings – The results showed that divorce in Cenggu Village was caused by three factors, namely: domestic violence, economic factors, and infidelity. The impact of divorced parents on children is that children become insecure when they are in the surrounding environment, divorce becomes a mental burden for children. Lack of attention and affection for children due to parental divorce causes feelings of anxiety, confusion, shame, and sadness. Meanwhile, regarding children's education after divorce, this is a shared responsibility, between a mother, father, family members, and the community in which they live. Research implications/limitations – Based on the results of the study, researchers recommend strengthening harmonious family values through socialization by related parties, for example the government through religious instructors.